상대적 성과에 따른 경영자 스톡옵션 - 김화성(Hwa Sung Kim) (한국증권학회지, 2010)
시장이 호황일 때 Black-Scholes 옵션 모형을 기반으로 한 기존의 경영자 스톡옵션이 경영자의 노력 이상으로 과도한 보상을 제공할 수 있음을 최근 연구들이 보고하고 있다. 따라서, 본 연구에서는 시장의 성과를 통제한 후에 기업의 기대성과보다 기업의 실제성과가 좋을 경우 경영자에게 보상을 제공하는 상대적 성과에 따른 경영자 스톡옵션 모형(relative performance-based executive stock option)을 제시하고자 한다. 이러한 가정 하에서 스톡옵션의 가치를 결정하였고, 기존의 스톡옵션과의 비교를 통해서 상대적 성과에 따른 스톡옵션이 기업의 성과에 보다 더 부합하는 옵션가치를 제공하는 것을 보였다. 또한, 스톡옵션의 인센티브 효과 분석을 통해서, 본 연구에서 제시한 새로운 스톡옵션이 주주와 경영자를 모두를 만족시키는 보상 수단이 될 수 있음을 보였다. According to recent studies, the existing executive stock option model provides executives with excessive rewards during market upturns. This paper suggests a relative performance-based executive stock option model with a positive payoff when the realized firm performance is better than the expected firm performance after controlling for the market performance. Under this assumption, we price a new kind of executive stock option. Compared with the existing executive stock option model, we show that the relative performance-based executive stock option model provides a price that fits the performance of a firm. Also, after analyzing incentive effects, we show that this new executive stock option can become a compensation which satisfies the interests of both shareholders and executives. KCI Citation Count: 1